The α-MEU model: a comment - Eichberger, Jürgen; Grant, Simon; Kelsey, David; Koševoj, Gleb A.; Ghirardato, Paolo; Maccheroni, Fabio; Marinacci, Massimo (Department of Economics discussion papers, 2009)
In [7] Ghirardato, Macheroni and Marinacci (GMM) propose a method for distinguishing between perceived ambiguity and the decision-maker's reaction to it. They study a general class of preferences which they refer to as invariant biseparable. This class includes CEU and MEU. They axiomatize a subclass of a-MEU preferences. If attention is restricted to finite state spaces, we show that any a-MEU preference relation, satisfies GMM's axioms if and only if a = D 0 or 1, that is, the preferences must be either maxmin or maxmax. We show by example that these axioms may be satisfied when the state space is [0,1].